Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
y = 27
Step-by-step explanation:
y/3 + 2 = 11
First subtract 2 from each side
y/3 + 2-2 = 11-2
y/3 = 9
Then multiply each side by 3
y/3 *3 = 9*3
y = 27
Answer:
Answer is below :)
Step-by-step explanation:
y/3 + 2 = 11 is the Expression
Only two steps:
step 1 = subtract 2 from both the sides
y/3 = 9
Step 2 = multiply 3 from both sides
y = 27
I hope this solved your question.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.